WISATA BUKIT PAL JEPANG SEBAGAI DAYA TARIK WISATA DI DESA SAPIT, KABUPATEN LOMBOK TIMUR - Danu Satria Prayuda; Lalu Yulendra; I Made Dayuh Hary Kosala; Desta Nur Maharani; Yuli Sawitri (Journal of Innovation Research and Knowledge, 2025)
This study is intended to identify the potential tourist attraction of of Pal Japan Hill and identify what factors influence its development, as well as formulate a strategy for developing the tourist attraction of Pal Japan Hill. The type of data used in this study is qualitative data. Sources of data used are primary and secondary data. Data collection techniques in this study were observation, interviews, documentation and FGD. The data analysis used in this research is SWOT analysis. This research answers the results of the three formulations of the problem, namely. From the results of this study, it is known that Pal Japan Hill in Sapit Village has a variety of tourism potential, both natural, cultural and artificial tourism which is very diverse and interesting to be developed as a tourist attraction in Sapit Village